“Atención de enfermería en paciente geriátrico con tuberculosis pulmonar recurrente” - Luna Risco, Madeline Andrea (2024)
Pulmonary tuberculosis is a disease caused by Mycobacterium tuberculosis, mainly affecting the lungs. Currently this disease does have treatment, however, it continues to be a public health problem. This study is about the case of an 81-year-old patient with reinfection of pulmonary tuberculosis. The main objective of the research is to apply nursing care to a geriatric patient with recurrent pulmonary tuberculosis. According to the identified dysfunctional patterns, a total of four care plans were developed focused on assistance with better pulmonary ventilation, nutritional counseling, education of the patient and their family about the disease, its complications, and the importance of adherence to treatment. The nursing interventions carried out in a patient with recurrent tuberculosis showed positive results in respiratory pattern, thermoregulation, healthy nutritional practices contributing to adequate weight gain, promotion of self-care and acceptance of her health status.